Antioxidant capabilities of Litsea Garciae bark extracts and their relation to the phytochemical compositions - Raduan, Siti Zaleha; Ahmed, Qamar Uddin; Kasmuri, Abdul Razak; Ahmad Rusmili, Muhamad Rusdi; Mia, Md Abdur Rashid; Wan Sulaiman, Wan Mohd Azizi; Mahmood, Muhammad Hamdi; Shaikh, Mohd Farooq (Malaysian Society of Applied Biology, 2022)
The plant species belonging to the Litsea genus are widely investigated due to their nutritional and medicinal purposes. In this regard, this study is another similar sincere effort in which the antioxidant property and phytochemical composition of Litsea garciae (L. garciae) bark’s hexane, chloroform, methanol, and aqueous extracts were evaluated to confirm its traditional benefits. The total flavonoid content (TFC) and total phenolic content (TPC) were determined first, followed by an assessment of in vitro antioxidant activity using the DPPH and FRAP assays. The composition of the secondary metabolites was determined using Ultra-High-Performance Liquid Chromatography-Mass Spectrometry (UHPLC-MS). As a result, methanol extract was recorded to have the highest TPC value aligned with its positive appearance in phytochemical screening. Its antioxidant capacity indicated the least IC50. The results indicated that the significant free radical scavenging activity was due to the methanolic extract’s high phenolic content. The secondary metabolites found in the methanol extract varied significantly according to UHPLC-MS analysis. The major phenolic compounds were found including N-trans-feruloyl-4-O-methyldopamine, N-cisferuloyltyramine, epicatechin-(4beta->6)-epicatechin-(2beta->7,4beta->8)-epicatechin, 7-Hydroxy-3-(4-methoxyphenyl)4-propyl-2H-1-benzopyran-2-one and 9-O-Methylneodunol. In general, the results indicate that L. garciae bark may be a promising source of novel natural compounds with antioxidative properties.